EVALUASI KELAYAKAN FINANSIAL DAN SENSITIVITAS USAHA TERNAK AYAM RAS PETELUR SIRUN FARM KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN - Safitri, Nindya Cahya; Affandi, Muhammad Irfan; Nugraha, Adia (Lampung University, 2024)
The objective of this research is to assess the financial feasibility and sensitivity of laying hens husbandry. The laying hens husbandry located at Sirun Farm in Natar District, South Lampung Regency, was the subject of this study. The data were gathered from July to October 2022. The sensitivity analysis and financial feasibility assessment employed to analyze the data. The study demonstrates that the development of laying hen husbandry has a favourable financial outlook. The initial cash outflow of the investment can be recovered in less than 10 years as indicated by the NPV of IDR 13,293,158,715. The gross B/C values is 1.63, while the net B/C values is 6.41. In addition, the Payback Period values is estimated to be 5.25 years, and the IRR values is 28.71 percent, which is higher than 6 percent interest rate. Based on the finding, of the sensitivity analysis, which was assumed a 9 percent decrease in chicken egg production and a 17 percent decrease in chicken egg sales, it is concluded that the laying hen industry is still worth to develop. Key words: evaluation, feasibility, financial, laying hens, sensitivity